Interaction peculiarities of age somatic indices and sport results of ski-racers, participants of olympic winter games - Cepulenas, A. (Biology of Sport, 2006)
The aim of the research - is to analyze interaction peculiarities of age somatic indices and sport result of ski-racers women and men. participants of Olympic Winter Games. Indices of age, height, body mass, Ketle index (g/cm), body mass index (kg/m2) of ski-racers women and men who participated in skiing competitions in XVIII Olympic Winter Games in Nagano and XIX Olympic Winter Games in Salt Lake City have been analyzed. Mean values (X) of age. some somatic indices and Standard indices divergence (+SD) of the most powerful skiing teams (National Teams), skiers - medal winners as well as skiers who won 1-10, 11-20, 21-30 places in separate distances are presented in the article. Age of skiers women (n=14) - medal winners in Nagano Olympic Winter Games was 28.40±4.0 years, height - I67.10±5.10 cm, body mass - 57.00+5.40 kg, Ketle index - 340.50±23.20 g/cm and indices of skiers women (n=l9) -medal winners in Salt Lake City Olympic Winter Games were analogous: age - 28.42±4.81 years, height - 168.84±5.08 cm. body mass - 59.05±5.76 kg, Ketle index - 349.22±27.22 g/cm. Age of skiers men - medal winners of Nagano Olympic Winter Games (n=16) was 29.8±4.0 years, height - 181.60±5.70 cm, body mass - 75.30±6.50 kg, Ketle index - 414.23±25.00 g/cm and indices of skiers men (n=21) - medal winners in Salt Lake City Olympic Winter Games were analogous: age -28.48±2.93 years, height -180.7115.3 cm, body mass - 73.7116.13 kg, Ketle index - 407.41±24.11 g/cm. Research results allow stating that height and body mass of skiers' women and men may be different. Possibilities to achieve high results have both tall and shorter as well as light and heavier skiers. Though body mass of men skiers and especially of women should be not heavy comparing with their height. Age, somatic indices of ski-racers women and men, Olympic medal winners, may be estimated as modeling and they may be used to make models for training high master ski-racers.